Penyelidikan analisis kandungan dalam bahan kurikulum bahasa - Noor Rohana Mansor (Kuala Terengganu, Terengganu : Penerbit UMT, Universiti Malaysia Terengganu, 2008)
Malay language learning methods in the Malaysian education
Revision of the author's thesis (Ph. D.)--Universiti Malaya
Includes bibliographical references (p. 125-141) and index
In Malay
Keywords: Education -- Research -- Methodology; Report writing